Energy use efficiency of crop residue management for sustainable energy and agriculture conservation in NW India. (August 2020) - Jat, H.S.; Jat, R.D.; Nanwal, R.K.; Lohan, Shiv Kumar; Yadav, A.K.; Poonia, Tanuja; Sharma, P.C.; Jat, M.L.
Abstract: In the Indo-Gangetic plains of South Asia, the triple challenges of diminishing farm profitability, deteriorating natural resources and energy deficits threaten conventional agricultural sustainability. This threat is intensified by the open field burning of crop residues that not only squander an indirect renewable source of energy but also impair the soil and environment quality. The crop residues can be used as organic manure by retaining the residues as mulch in the field. After a long term (5-yrs) study, it was concluded that crop residues biomass contributed maximum (∼79%) in total input energy (1, 68, 556 MJ ha −1 ) in conservation agriculture (CA) based systems, however fertilizer application (non-renewable energy source) contributed maximum (∼50%) to the total energy (40, 636 MJ ha −1 ) in conventional tillage (CT) based maize-wheat cropping system.CA based maize systems recorded higher input energy and energy intensiveness by 23 and 57% respectively, and recorded almost 44% lower energy use efficiency and energy productivity compared to CT based maize systems. On 5 years average basis, Zero tillage based maize-wheat-mungbean with nutrient expert cropping system(ZT/MWMb + NE) utilized 351% more input energy, which resulted in25%higher output energy and 363% higher EI compared to CT/MW (40, 636 MJ ha −1, 4, 20, 197 MJ ha −1, 39.60 MJ USD −1 ). Highlights: In CA systems, crop residues contributed 79% in total energy input. Maize-wheat-mungbean cropping system was found best w.r.t. the energy indices in N–W India. CA-based systems enhanced farm profitability by ∼50%. The system productivity improved by ∼25% in CA based management. With the use of nutrient expert system 25% higher output energy achieved.